Possibility of the usage of active media with electron beams for ion acceleration - Lymar, A.G. (Вопросы атомной науки и техники, 2008)
Brief analysis of publications, which have aroused considerable interest in physics of virtual cathode (VC) in connection with the problem of ions acceleration by electron beams (EB), results of distributed VC numeral simulation and variants of the systems in which the distributed VC can be used for acceleration of ions are presented. Приведені короткий аналіз публікацій, які визначили інтерес до фізики віртуального катода (ВК) у зв'язку з проблемою прискорення іонів електронними потоками (ЕП), результати чисельного моделювання поведінки розподіленого ВК і варіанти систем, в яких розподілений ВК може бути використаний для прискорення іонів. Приведены краткий анализ публикаций, которые определили интерес к физике виртуального катода (ВК) в связи с проблемой ускорения ионов электронными потоками (ЭП), результаты численного моделирования поведения распределенного ВК и варианты систем, в которых распределенный ВК может быть использован для ускорения ионов.